Pimarane Diterpenes from Fungi - Ke Ye; Hong-lian Ai (MDPI AG, 2022)
Pimarane diterpenes are a kind of tricyclic diterpene, generally isolated from plant and fungi. In nature, fungi distribute widely and there are nearly two to three million species. They provide many secondary metabolites, including pimarane diterpenes, with novel skeletons and bioactivities. These natural products from fungi have the potential to be developed into clinical medicines. Herein, the structures and bioactivities of 197 pimarane diterpenes are summarized and the biosynthesis and pharmacological researches of pimarane diterpenes are introduced. This review may be useful improving the understanding of pimarane diterpenes from fungi.